(untitled) (Research, Society and Development, 2022)
The worldwide incidence of childhood cancer increases every year. The treatment of neoplasms includes different modalities, highlighting the use of antineoplastic chemotherapy in a predominantly outpatient manner. The activities developed in the chemotherapy outpatient clinic need to be organized through flows for the optimization of care during the period of operation of the sector, seeking to meet safety requirements given the complexity of chemotherapy protocols and also customer satisfaction. The objective of this work is to report the flow of care established in an outpatient chemotherapy clinic. This is an experience report, lived by the authors in the management of a pediatric chemotherapy clinic located in a reference unit for cancer treatment in the State of Rio de Janeiro. The organization of the flow in the different stages that involve outpatient care for chemotherapy is fundamental, since it includes essential steps for patient safety and quality of care.